2021
DOI: 10.15252/embj.2020106317
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic ACVR1R206H activation by Activin A‐induced receptor clustering and autophosphorylation

Abstract: Fibrodysplasia ossificans progressiva (FOP) and diffuse intrinsic pontine glioma (DIPG) are debilitating diseases that share causal mutations in ACVR1, a TGF-β family type I receptor. ACVR1 R206H is a frequent mutation in both diseases. Pathogenic signaling via the SMAD1/5 pathway is mediated by Activin A, but how the mutation triggers aberrant signaling is not known. We show that ACVR1 is essential for Activin A-mediated SMAD1/5 phosphorylation and is activated by two distinct mechanisms. Wild-type ACVR1 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 74 publications
6
49
0
Order By: Relevance
“…However, it should be noted that whilst statistically significant the increase in survival was only modest, with both drugs increasing survival by 15 days [ 151 ]. The in vitro efficacy of LDN-193189 in DMGs has been observed by others, with some evidence of improved efficiency in ACVR1 -mutant cells above those of the wild type; in contrast, another study into LDN-214117 found no significant effect on DMGs in vitro [ 107 , 153 , 155 ]. However, several analogues of LDN-214117 have been developed which exhibit a profile with increased potency, selectivity and BBB permeability.…”
Section: Targeting Cellular Signalling Pathways In Dmgsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, it should be noted that whilst statistically significant the increase in survival was only modest, with both drugs increasing survival by 15 days [ 151 ]. The in vitro efficacy of LDN-193189 in DMGs has been observed by others, with some evidence of improved efficiency in ACVR1 -mutant cells above those of the wild type; in contrast, another study into LDN-214117 found no significant effect on DMGs in vitro [ 107 , 153 , 155 ]. However, several analogues of LDN-214117 have been developed which exhibit a profile with increased potency, selectivity and BBB permeability.…”
Section: Targeting Cellular Signalling Pathways In Dmgsmentioning
confidence: 64%
“…ACVR1 mutations result in hyperactivity in response to BMP ligands and constitutive BMP signalling, independent of ligand binding [ 148 , 149 , 150 ]. Furthermore, activin A promotes SMAD1/5/8 signalling in ACVR1 mutated cells at even low ligand concentrations as a result of activin A forming ACVR2A/B–ACVR1R206H complexes [ 151 , 152 , 153 , 154 ]. ACVR1 mutations in DMGs are associated with upregulated SMAD1/5/8 signalling and increases in cell proliferation, indicating an oncogenic role for the BMP pathway in this context [ 107 , 151 , 155 ].…”
Section: Targeting Cellular Signalling Pathways In Dmgsmentioning
confidence: 99%
“…Here, we aimed to visualize receptor dependent Activin A binding on living transfected COS-7 cells in a fluorescence-based approach. Fluorescently labeled Activin A was recently used to show ACVR2B clustering (Ramachandran et al, 2021). Accordingly, we have labeled Activin A with Cy5 and established an analysis pipeline for assessment of Activin A-Cy5 binding on COS-7 cells dependent on the expression of various Halo-tagged receptors ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent examples include the determination of SNAP-mGluR4 co-localization (with Ca v 2.1 and Bassoon) by two-color dSTORM microscopy (Siddig et al, 2020), the compositional diversity of differently tagged-kainate receptor assembly by three-color single molecule TIRF microscopy (Selvakumar et al, 2021), and the endocytosis and turnover of Halo-TfR by widefield imaging (Jonker et al, 2020). Alternatively, visualization of cell surface ligand binding, endo- and exocytosis, as well as receptor clustering was achieved using ligands covalently linked to fluorophores (Alborzinia et al, 2013; Ast et al, 2020; Nanda & Lorsch, 2014; Paarmann et al, 2016; Ramachandran et al, 2021; Trujillo et al, 2020). For this, ligands were either directly labeled at deprotonated primary amines using NHS-activated fluorophores (Alborzinia et al, 2013; Nanda & Lorsch, 2014), or through introduction of an N- or C-terminal cysteine residue allowing for site-directed maleimide coupling of the dyes (Ast et al, 2020; Paarmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation